2019
DOI: 10.1111/jpn.13191
|View full text |Cite
|
Sign up to set email alerts
|

Metabolisable energy intake and growth of privately owned growing dogs in comparison with official recommendations on the growth curve and energy supply

Abstract: The correct assumption of metabolisable energy (ME) requirement is essential for the nutrition consultation and diet formulation. In young dogs, too high energy supply can accelerate growth and thus lead to developmental orthopaedic diseases. The aim of the present study was to collect the data on ME intake and body weight (BW) development in privately owned growing dogs in order to compare these data with the current recommendations. Our hypothesis was that the actual ME intake of healthy young dogs would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Similarly, the average MER of pet dogs was demonstrated to be 519 ± 159 kJ/kg 0.75 per day [ 65 ]. Importantly, the data presented here are consistent with studies that demonstrate collectively that the NRC recommendation overestimates the amount of energy required for healthy growth across multiple breeds [ 27 , 39 , 40 , 66 , 67 ]. Indeed, breed specific differences in energy requirements, especially between different sized breeds, have been documented, with Alexander et al (2017) showing differences between the energy requirements of Yorkshire terriers, miniature schnauzers and Labrador retrievers.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, the average MER of pet dogs was demonstrated to be 519 ± 159 kJ/kg 0.75 per day [ 65 ]. Importantly, the data presented here are consistent with studies that demonstrate collectively that the NRC recommendation overestimates the amount of energy required for healthy growth across multiple breeds [ 27 , 39 , 40 , 66 , 67 ]. Indeed, breed specific differences in energy requirements, especially between different sized breeds, have been documented, with Alexander et al (2017) showing differences between the energy requirements of Yorkshire terriers, miniature schnauzers and Labrador retrievers.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, Dobenecker et al (2013) showed a difference in energy requirements between foxhound-boxer-Ingelheim Labrador mixed breed puppies and beagle puppies up to 28 weeks of age. A large-scale study of client owned puppies reported that weaned puppies younger than 6 months had energy intakes that were approximately 80% of the NRC (2006) recommendation and in older puppies approximately 88% of this recommendation [ 39 ]. Collectively these studies suggest that breed differences in energy requirements should be considered when recommending feeding amounts during growth and the NRC (2006) universal equation is not suitable for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation